2012
DOI: 10.1016/s0140-6736(11)61294-4
|View full text |Cite|
|
Sign up to set email alerts
|

Self-monitoring of oral anticoagulation: systematic review and meta-analysis of individual patient data

Abstract: SummaryBackground Uptake of self-testing and self-management of oral anticoagulation has remained inconsistent, despite good evidence of their eff ectiveness. To clarify the value of self-monitoring of oral anticoagulation, we did a metaanalysis of individual patient data addressing several important gaps in the evidence, including an estimate of the eff ect on time to death, fi rst major haemorrhage, and thromboembolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
255
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(278 citation statements)
references
References 46 publications
9
255
1
13
Order By: Relevance
“…This number was chosen to be consistent with the trials from which the relative effect estimates for self-monitoring were obtained. In a recent meta-analysis of patient-level data, 108 11 of the self-monitoring trials included in our review reported the mean increase in the number of tests performed with self-monitoring versus control. There was an average of 24 additional tests by 12 months for people with atrial fibrillation and 22 additional tests for people with an AHV.…”
Section: Costs Of Self-monitoringmentioning
confidence: 94%
See 2 more Smart Citations
“…This number was chosen to be consistent with the trials from which the relative effect estimates for self-monitoring were obtained. In a recent meta-analysis of patient-level data, 108 11 of the self-monitoring trials included in our review reported the mean increase in the number of tests performed with self-monitoring versus control. There was an average of 24 additional tests by 12 months for people with atrial fibrillation and 22 additional tests for people with an AHV.…”
Section: Costs Of Self-monitoringmentioning
confidence: 94%
“…108 Heneghan and colleagues 108 presented a subgroup analysis where they presented the estimated pooled hazard ratio and number needed to treat to prevent one major thromboembolic event (ischaemic stroke and systemic embolism) and one major haemorrhagic event by year of follow-up (up to 5 years) based on 2243 people with an AHV. The formula used by Heneghan and colleagues 108 to estimate the number needed to treat was:…”
Section: Assessment Of Cost-effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…If PST actually does reduce major events, then the ICER would be even more attractive for PST, and possibly even dominant (i.e., offering better outcomes at lower costs). 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews have supported frequent home monitoring via patient self-testing (PST) of INR as a safe and effective alternative to standard in-clinic testing. 6,[8][9][10] In 2012, the American College of Chest Physicians revised its clinical practice guidelines to incorporate the use of portable at-home INR testing devices. 11 The Home INR Study (THINRS), the largest randomized controlled trial of PST (n = 2922) to date, found negligible differences in clinical outcomes between weekly PST and once-monthly in-clinic testing via HQACM.…”
Section: Introductionmentioning
confidence: 99%